The ideal model of waqf financing - Furqon, Ahmad (Journal of Islamic Economics Management and Business (JIEMB), 2020)
Purpose – The aim of this research is to find out the financing mechanism or the waqf assets funding done by nazhir and to find the ideal mechanism for the development of waqf assets.Method – This is a qualitative research with a case study approach. The research object was selected using purposive sampling, namely nazhir waqf in Central Java which manages productive waqf including: Sultan Agung Waqf Foundation (YBWSA), Semarang Grand Mosque Management Agency (BPMAS), and Pekalongan City Muslimin Foundation (YMKP).Result – This study found that the Sultan Agung Waqf Foundation (YBWSA) implements a mechanism for waqf financing in the form of public funding, government assistance, murabahah, and ijarah. BPMAS implements a waqf financing mechanism in the form of donations & alms, government assistance, ijarah, and cash waqf. Meanwhile, YMKP provides financing for the development of its waqf assets in the form of government assistance and qardul hasan. Implication – This study can be used by government, policy maker, business party, or scholar to create an optimal and ideal mechanism in developing waqf assets.Originality – In the past, studies of waqf asset management were performed in the context of middle east, mostly Kuwait. This study provides waqf asset management in context of South East region.